"Untold Stories to Tell": Making Space For The Voices of Youth Songwriters. Issue 5 (31st January 2013) - Williams, Wendy R.
Abstract This article shares findings from case studies of two eighteen‐year‐old songwriters, Bradley and James. The study investigated songwriter motivation, writing methods, and school experiences. Data was collected over the course of one year through two in‐depth interviews per songwriter, two teacher interviews, and 101 songwriting artifacts. Grounded theory and constant comparison methods were used during data analysis. This study found that Bradley's and James's music emphasizes acceptance of others and critical engagement with social issues. They see songwriting as a masculine alternative to journaling, and they have strong preferences regarding their writing tools, time, and spaces. Additionally, these songwriters prefer to write one line at a time, to skip pre‐writing, and to have a choice of topic—preferences that sometimes conflicted with their school experiences. This article concludes by offering suggestions for supporting songwriting in school.